A Comparison Study of Two 3-UPU Translational Parallel Manipulators. (9th April 2013) - Hu, Bo; Yao, Yunfeng; Wu, Peiliang; Lu, Yi
A comparison study of two 3-UPU translational parallel manipulators (PMs) is investigated in this paper. The two 3-UPU PMs have identical pure translational degree of freedoms (DOFs) and an identical actuator arrangement, and thus have identical kinematics. But some differences between the two translational 3-UPU PMs impliedly exist. The two PMs differ in terms of singularity configuration, constrained forces/torques situations and stiffness. This paper focuses on discussing the differences between the two translational 3-UPU PMs. This study provides insights into PMs with identical kinematics.